2019
DOI: 10.1016/j.ijpp.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

An isotopic case study of individuals with syphilis from the pathological-anatomical reference collection of the national museum in Prague (Czech Republic, 19th century A.D.)

Abstract: Objective: This paper aims at investigating the possible existence of isotopic offsets in δ 13 C col and δ 15 N col values in relation to tertiary syphilis. Material: Based on materials from the 19th c. A.D. deriving from the pathological-anatomical reference collection (the Jedlička collection) of the National Museum in Prague (Czech Republic), a comparative approach of ten individuals with syphilis and nine without the disease was undertaken. Methods: Bone powder samples were defatted according to the protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 123 publications
(161 reference statements)
1
13
0
Order By: Relevance
“…It is true that negative peaks in δ 13 C show slightly earlier timing than those in δ 15 N. This fits the hypothesis of Salesse et al (2019), whose data suggested that carbon balance may become negative more rapidly than nitrogen, and thus, δ 13 C may be more sensitive to milder forms of nutritional stress. In later stages of undernutrition, δ 13 C may rise again as the body runs out of 13 C depleted fat reserves (Neuberger et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…It is true that negative peaks in δ 13 C show slightly earlier timing than those in δ 15 N. This fits the hypothesis of Salesse et al (2019), whose data suggested that carbon balance may become negative more rapidly than nitrogen, and thus, δ 13 C may be more sensitive to milder forms of nutritional stress. In later stages of undernutrition, δ 13 C may rise again as the body runs out of 13 C depleted fat reserves (Neuberger et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Particles ranging between 0.3 and 0.7 mm were collected for collagen extraction, and those less than 0.3 mm were used for carbon and oxygen isotope analyses of bioapatite carbonates. Prior to the purification procedures, bone powder samples were defatted according to the protocol developed by Kates [ 75 ] and tested by Liden et al [ 76 ], as presented in Salesse et al [ 77 ]. Bone collagen was extracted following the non-ultrafiltered procedure proposed by Brock et al [ 78 ] while unburnt bone carbonate samples were prepared following a revised version of the protocol of Balasse et al [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…Few isotopic studies of bone collagen have included individuals diagnosed with suspected treponematosis (Dent, ; Mays, Crane‐Kramer, & Bayliss, ; Mays, Vincent, & Meadows, ; Rissech et al, ; Santos, Gardner, & Allsworth‐Jones, ; Schwarz, Skytte, & Rasmussen, ); even fewer have sought to compare these values directly with other bones or individuals exhibiting no signs of the disease to discern any potential pathophysiological effects associated with treponemal infection (Salesse, Kaupová, Brůžek, Kuželka, & Velemínský, ). Slightly lower δ 13 C col values (0.3–0.4‰) noted among 19th‐century people with syphilis, relative to unaffected individuals, were attributed to either prescribed dietary change or to nutritional stress—possibly resulting in endogenously‐formed nonessential amino acids derived from nonprotein sources depleted in 13 C—but not to the pathophysiology of the disease itself (Salesse et al, ). Nitrogen isotope values in the same group remained unchanged (Salesse et al, ).…”
Section: Archaeometry and Archaeological Biogeochemistrymentioning
confidence: 99%
“…Slightly lower δ 13 C col values (0.3–0.4‰) noted among 19th‐century people with syphilis, relative to unaffected individuals, were attributed to either prescribed dietary change or to nutritional stress—possibly resulting in endogenously‐formed nonessential amino acids derived from nonprotein sources depleted in 13 C—but not to the pathophysiology of the disease itself (Salesse et al, ). Nitrogen isotope values in the same group remained unchanged (Salesse et al, ). Oxygen isotope values from hydroxyapatite also have the potential to be modified by disease due to imbalances during respiration or modified basal metabolic rates; however, 18 O depletion associated with anemia identified in one human study was attributed not to pathophysiological change but to changes in diet (Carroll, Inskip, & Waters‐Rist, ).…”
Section: Archaeometry and Archaeological Biogeochemistrymentioning
confidence: 99%
See 1 more Smart Citation